O3B.6 The economic burden of work-related asbestos exposure. (April 2019) - Tompa, Emile; Kalcevich, Christina; McLeod, Christopher; Lebeau, Martin; Song, Chaojie; Kim, Joanne; Demers, Paul
Abstract : The objective of this study was to estimate the economic burden of lung cancer and mesothelioma due to occupational and paraoccupational asbestos exposure in Canada. We estimated the lifetime cost of newly diagnosed lung cancer and mesothelioma cases associated with occupational and para-occupational asbestos exposure for calendar year 2011 based on the societal perspective. The key cost components considered were healthcare costs, productivity and output costs, and quality of life costs. There were 427 cases of newly diagnosed mesothelioma cases and 1904 lung cancer cases attributable to asbestos exposure in our reference year—calendar year 2011—for a total of 2331 cases. Our estimate of the economic burden is C831 million in direct and indirect costs for newly identified cases of mesothelioma and lung cancer and C1.5 billion in quality of life costs based on a value of C100, 000 per quality-adjusted life year. This amounts to C356, 429 and C652, 369 per case, respectively. The economic burden of lung cancer and mesothelioma associated with occupational and para-occupational asbestos exposure is substantial. The estimate identified is for 2331 newly diagnosed, occupational and para-occupational exposure cases in 2011, so it is only a portion of the burden of existing cases in that year. Our findings provide important information for policy decision makers for priority setting, in particular the merits of banning the mining of asbestos and use of products containing asbestos in countries where they are still allowed and also the merits of asbestos removal in older buildings with asbestos insulation.